ANALISIS FAKTOR RISIKO DISMENORE PRIMER DAN DISMENORE SEKUNDER PADA MAHASISWI - Putra, Amrullah Syah; Saputra, Nicko Pisceski Kusika; Noviardi, Noviardi; Ismawati, Ismawati (Media Penelitian dan Pengembangan Kesehatan, 2024)
While the incidence of dysmenorrhea is relatively high worldwide, the prevalence of dysmenorrhea reported in the literature varies substantially. This study aimed to analyze the risk factors for primary dysmenorrhea and secondary dysmenorrhea. This research is a cross analytical design. The sample in this study was all medical faculty students at Riau University in 2019-2022, namely 410 people. From the research results, it was found that there was a relationship between menstrual blood volume, history of food allergies and stress with the incidence of primary dysmenorrhea. Meanwhile, the incidence of secondary dysmenorrhea was related to age, menstrual cycle, history of the sample's gestational age at birth, history of low birth weight (LBW), history of emotional violence, stress and birth history of samples from preeclamptic mothers at the time of delivery. This research concluded that there were several significant findings regarding factors related to the occurrence of dysmenorrhea in Riau University medical students in 2019 - 2022. The research showed the importance of paying attention to factors such as the length of the menstrual cycle, history of food allergies, history of emotional violence, stress, and history of maternal preeclampsia in efforts to prevent and manage dysmenorrhea in the population. It is recommended that future research further explore the association between the identified risk factors and the incidence of dysmenorrhea, potentially revealing additional insights to guide clinical practice and public health initiatives.